2011
DOI: 10.1158/1535-7163.mct-11-0356
|View full text |Cite
|
Sign up to set email alerts
|

The Clinically Active PARP Inhibitor AG014699 Ameliorates Cardiotoxicity but Does Not Enhance the Efficacy of Doxorubicin, despite Improving Tumor Perfusion and Radiation Response in Mice

Abstract: AG014699 was the first inhibitor of the DNA repair enzyme PARP-1 to enter clinical trial in cancer patients. In addition to enhancing the cytotoxic effect of DNA-damaging chemotherapies, we have previously shown that AG014699 is vasoactive, thereby having the potential to improve drug biodistribution. The effectiveness of the clinical agent doxorubicin is confounded both by poor tumor penetration and cardiotoxicity elicited via PARP hyperactivation. In this study, we analyzed the impact of AG014699 on doxorubi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 37 publications
(49 reference statements)
2
42
0
Order By: Relevance
“…Temozolomide (TMZ) is a DNA alkylating agent and is used as a standard-of-care treatment for patients with glioblastoma 13 . Here we used the colorectal cancer cell line SW620 that we knew was sensitive to alkylating agents ( Figure 5a) and which has been used in xenograft studies in combination with TMZ and the PARP inhibitors olaparib or AG014699 14, 15 . First we used the same assay conditions to determine whether increasing concentrations of TMZ induced PAR chains that could be maintained by inhibiting PARG with a potent inhibitor (compound 8 from Figure 3d).…”
Section: Resultsmentioning
confidence: 99%
“…Temozolomide (TMZ) is a DNA alkylating agent and is used as a standard-of-care treatment for patients with glioblastoma 13 . Here we used the colorectal cancer cell line SW620 that we knew was sensitive to alkylating agents ( Figure 5a) and which has been used in xenograft studies in combination with TMZ and the PARP inhibitors olaparib or AG014699 14, 15 . First we used the same assay conditions to determine whether increasing concentrations of TMZ induced PAR chains that could be maintained by inhibiting PARG with a potent inhibitor (compound 8 from Figure 3d).…”
Section: Resultsmentioning
confidence: 99%
“…A number of PARP inhibitors (ABT-888/Veliparib, AZD-2281/Olaparib, AG014699/ Rucaparib, MK-4827/Niraparib, AG14361, GPI-15427, E7016) have been shown to enhance tumour sensitivity to radiation in syngeneic and xenograft models of breast [79,80], colon [81][82][83], lung [79,84,85], nasopharyngeal [86], head and neck [87], and brain tumours [88][89][90][91] (Table 11.1). PARP inhibition combined with Colon carcinoma (SW620, LoVo) AG14361, i.p., 30 min before X-rays (5 or ionising radiation resulted in delayed tumour growth and extended median survival time.…”
Section: In Vivo Radiation Sensitivity After Parp Inhibition: Additiomentioning
confidence: 99%
“…Nicotinamide is well known to act as a vasodilator [89], suggesting that other PARP inhibitors, which are structurally similar to nicotinamide could also improve vessel perfusion and potentially increase drug delivery to adjacent tumour tissues. Recent studies have demonstrated that PARP inhibitors (AG014699 and Olaparib) significantly increase the cytotoxic effect of radiotherapy in vivo and in vitro [90,91] (Chap. 12).…”
Section: Increasing Drug Delivery To Hypoxic Regionsmentioning
confidence: 99%